EVERYDAY EXCLUSION FROM THE INFORMATION SOCIETY: DIGITAL INEQUALITIES, IDENTITY WORK, AND EMOTION MANAGEMENT - Robinson, Laura (AoIR Selected Papers of Internet Research, 2015)
Based on in-depth interviews in an agricultural community in California, this research examines everyday digital exclusion as it is experienced by socio-economically disadvantaged youth. The findings reveal how youths without resources occupy a liminal digital zone necessitating special kinds of identity performances (Goffman, 1959) and emotion management (Hochschild, 1979) unnecessary for their digitally advantaged peers. Regarding identity work, the examination takes a Symbolic Interactionist approach to explore digitally disadvantaged youths’ identity work and interactional strategies to cope with quotidian resource shortages. Concerning emotion management, the analysis reveals how disadvantaged youth work to suppress negative emotions created by the pressure to ‘keep up’ with their better-resourced peers. In making these connections, the research makes a distinct contribution to the literature on new media and everyday life by forging links between the emergent field of digital inequality with the established literatures on Symbolic Interactionist identity work and emotion management.